THE INFLUENCE OF GREEN ACCOUNTING ON FINANCIAL PERFORMANCE AND CORPORATE SUSTAINABILITY: STRATEGIC ACCOUNTING MANAGEMENT PERSPECTIVE - Henny Rakhmawati (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to analyze the effect of green accounting implementation on financial performance and corporate sustainability from the perspective of strategic accounting management. In an era of business that increasingly demands environmental responsibility, green accounting is seen as an innovative approach that not only records environmental costs but also integrates sustainability aspects into corporate strategy. This study uses a quantitative approach with data collected from manufacturing companies in Indonesia that have implemented green accounting practices. The results of the study indicate that green accounting contributes positively to corporate financial performance through cost efficiency and improved reputation in the eyes of stakeholders. In addition, this practice has been shown to strengthen the company's sustainability position by increasing compliance with environmental regulations and creating long-term value. These findings emphasize the importance of the role of strategic accounting management in designing and implementing environmental policies that are aligned with the company's financial and sustainability goals. The practical implications of this study encourage companies to make green accounting an integral part of their business strategy in order to create sustainable competitive advantage.